1997
DOI: 10.1183/09031936.97.10112515
|View full text |Cite
|
Sign up to set email alerts
|

Annual variability in methacholine responsiveness in nonasthmatic working adults

Abstract: Change in airway responsiveness is used frequently as a clinical as well as an epidemiological tool. Changes in airway responsiveness can be superior to other measures of lung function in that they are more sensitive indicators of an environmental effect. However, normal variation in test results must be defined before change can be interpreted.To characterize annual variability in airways responsiveness, we administered a high-dose methacholine challenge at 1 yr intervals for up to 4 yrs to 105 healthy, nonas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…4 New results including an extra follow up survey gave an overall ICC of 0.37, with a within person standard deviation of 1.0 doubling concentrations that was comparable to other studies, but lower between person variation. An ICC of 0.45 for PD 20 was obtained by Beckett et al, 30 with the largest within person standard deviation of any study. The third study, carried out in general practice, found an ICC of 0.48 for 27 subjects with complete data and measurable PD 20 on six occasions, but higher ICCs (0.56 and 0.68) when all first year and all second year pairs were analysed.…”
Section: Long Term Repeatabilitymentioning
confidence: 59%
See 1 more Smart Citation
“…4 New results including an extra follow up survey gave an overall ICC of 0.37, with a within person standard deviation of 1.0 doubling concentrations that was comparable to other studies, but lower between person variation. An ICC of 0.45 for PD 20 was obtained by Beckett et al, 30 with the largest within person standard deviation of any study. The third study, carried out in general practice, found an ICC of 0.48 for 27 subjects with complete data and measurable PD 20 on six occasions, but higher ICCs (0.56 and 0.68) when all first year and all second year pairs were analysed.…”
Section: Long Term Repeatabilitymentioning
confidence: 59%
“…The one population study of short term repeatability had a within person standard deviation in line with short term studies of asthmatic patients 13 23 but also with the long term Vlagtwedden/ Vlaardingen study (table 4), while the long term population study of Beckett et al had greater within person variation. 30 Hence, the effect of selection of subjects on between person variation and the effect of length of follow up on within person variation both influence the ICC. However, restriction of data to participants with two measurable PD 20 values decreases between person variation and hence the ICC.…”
Section: Variation In Iccmentioning
confidence: 99%
“…The reason for the poor reproducibility is not clear however environmental factors and/or physiological variation impacts significantly on variability (37). Airway calibre fluctuates throughout the day and over short-term periods (38).…”
Section: Discussionmentioning
confidence: 99%
“…Beckett et al [1997] examined methacholine responses among a group of 105 nonasthmatic adults at 1 year intervals for up to 4 years. At least 30% of the participants had an annual change in methacholine responsiveness of one or more doubling doses.…”
Section: Technical Factors Which May Affect Methacholine Challenge Tementioning
confidence: 99%